Presynaptic axonal amyloid-β induces caspase-3 activation and neurodegeneration in the postsynaptic neuron - Kása, Péter (Acta Biologica Szegediensis, 2004)
It is assumed that the amyloid-beta peptide (Ab) contributes to the neurodegeneration in Alzheimer’s disease (AD). Activation of an apoptotic pathway may play a key role in this process. The apoptotic signal may be driven by caspases. The presynaptic Ab protein may be an activator of caspase-3 and could initiate a series of cascade events, which results in neurofibrillary degeneration in a postsynaptic cell. We report here that the axonic Ab in the AD brain may be associated with caspase-3 activation. Our data suggest that caspase-3 in fact has a significant role in the widespread neuronal cell death that occurs in AD brain. A subset of pyramidal cells in hippocampus area CA1 demonstrated widespread accumulation of tau-protein. Individual postsynaptic neurons contained intracellular activated caspase-3 and were co-localized with neurofibrillary tangles. The results presented here support the suggestion that caspase-3 activation may lead to the neuronal cell death associated with AD. However, we are aware that, besides Ab, other factors too may initiate a series of events which lead to the development of neurofibrillary tangles in the postsynaptic neurons.